Goal setting in physical education and sports sector - Sazonova, S.L.; Simonova, A.K. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to theoretically substantiate the goal setting technology application in sports and offer a goal setting application algorithm to facilitate competitive progress. Methods and structure of the study. We run, for the purposes of the study, psychological tests to rate the goal setting situation and potential progress in sampled athletes (n=40). The test set included: (1) Goal-Methods-Result test to rate the individual predispositions for purposeful actions and profile the individual goal setting skills and specifics; and (2) Self-esteem rating test. Results and conclusion. The study demonstrates benefits of the goal setting technology application for success in sports, provided it is well designed and managed at every training stage to help the athlete develop the need and skills for self-reliant persistent goal setting for the individual and group progress. Determined goal setting practicing helps develop a range of qualities critical for success including determination, responsibility, efficiency, decision-making, progress management and forecast skills. Benefits of a prudent goal setting technology are particularly clear and fast in the physical education and sport sector, since an athletic progress take relatively little time when prudently designed and managed so as to efficiently set specific goals in the growth process taking into account the individual and socio-psychological specifics at every progress stage. The goal setting algorithm should be applicable for very specific progress missions to be effective. Prudent training process design should consider clear goal setting as a starting point for success and a key element in the professional service of every sports trainer.